Chemotherapy-induced nausea and vomiting: Exploring patients’ subjective experience - Pei Lin, Lua; Nik Mazlan, Mamat; Noor Salihah, - (Dove Medical Press Ltd., 2016)
Background: This study aimed to explore the subjective experience of nausea and vomiting during chemotherapy treatment among breast cancer patients and the impacts on their daily lives.